2016
DOI: 10.3168/jds.2015-10820
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction for the interval from calving to first insemination with regard to calving month and geographic location in Holstein cows in Denmark and Sweden

Abstract: The objectives of this study were to investigate genotype by environment interaction effects, with environments defined as calving month and geographic location, on the interval from calving to first insemination (CFI) of Holstein cows in Denmark and Sweden. The data set included 811,285 records on CFI for first-parity cows from January 2010 to January 2014 housed in 7,458 herds. The longest mean CFI was 84.7 d for cows calving in April and the shortest was 76.3 d for cows calving in September. The longest mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Some previous studies have reported the existence of G × E interactions in different fertility traits for cows under different environmental descriptors. For instance, ICF was found to have a high sensitivity under different calving months in Danish and Swedish Holstein dairy cattle (Ismael et al 2016). Significant G × E interactions in different herds of conventional and organic production systems were observed for calving interval, days open and pregnant at first insemination only in the second parity of Swedish Holsteins (Sundberg et al 2010), but no G × E interactions existed in the first parity.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported the existence of G × E interactions in different fertility traits for cows under different environmental descriptors. For instance, ICF was found to have a high sensitivity under different calving months in Danish and Swedish Holstein dairy cattle (Ismael et al 2016). Significant G × E interactions in different herds of conventional and organic production systems were observed for calving interval, days open and pregnant at first insemination only in the second parity of Swedish Holsteins (Sundberg et al 2010), but no G × E interactions existed in the first parity.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because, according to Kolmodin et al [18], alterations in the average rainfall exert little or no effect on the PY, reducing the effects of environmental variance on the total component. However, latitudinal differences have been cited in the literature as the principal reason for the alterations in temperature and time of day [19]. Carabaño et al [20] pointed out that temperature can be a determinant factor that influences the interaction on the production of protein in milk.…”
Section: Discussionmentioning
confidence: 99%
“…The progeny performance of these bulls can be different in tropical and temperate countries, and the objectives and selection criteria are different, requiring the use of bulls that are produced and evaluated in tropical conditions, selected for production, and adapted to the local environment. Ismael et al. (2016b) found no reclassification of Holstein bulls along the environmental gradient in Danish herds and considered GEI to be zero.…”
Section: Resultsmentioning
confidence: 95%
“… Ouweltjes, Windig, Van Pelt and Callus (2015) also found a tendency of higher heritability in less favorable environments when evaluating calf mortality rate in first-calving dairy cows in the Netherlands; they found two-fold the heritability for unfavorable environments when compared to favorable environments. Similarly, Ismael et al. (2016b) estimated two-fold lower heritability in the most favorable environments when assessing the fertility of Holstein cows in Denmark.…”
Section: Resultsmentioning
confidence: 96%